Gracious glutinous rice - Corpus, Arlene May G. (Health & Home, 2017)
[This article explains what Filipino glutinous rice (a.k.a. malagkit) is, which is described as a delicacy made of short-grain rice and is known to be sticky and because of a larger amount of amylopectin starch, compared to ordinary types of rice. Because it is made of short-grain rice, it requires less water to cook and turns soft, sticky, and transparent. It can either be chewy and sticky if steamed or have a soft, mushy texture if boiled. Malagkit can either be eaten out of hand or along soups or stews. It also contains some amounts of vitamins and minerals and provides calories and carbohydrates to the body, and, because it does not contain any dietary gluten, it can included in gluten-free diets. The article also includes a short recipe on how to make sweet potato and red mung beans buchi]